Does Knowledge Empower? Education, Legal Awareness and Intimate Partner Violence - Bilge Erten; Pinar Keskin (Institute of Labor Economics (IZA), 2021)
This paper uses an extension of compulsory schooling in Turkey to estimate the causal effects of education on women's legal awareness of laws that were designed to reduce gender inequality and prevent domestic violence. By implementing a regression discontinuity design, we find that the reform-induced increase in female education improved legal awareness. Women exposed to the reform were more likely to have heard about the new laws and services through newspapers, journals, or books. However, despite these improvements in women's legal awareness, we find no evidence of a significant change in the risk of experiencing domestic violence or ability to quit abusive relationships.
Keywords: J12; J16; I25; 330; domestic violence; education; information acquisition; legal knowledge; regression discontinuity